Clinical Activity of Behcet’s Disease Associated with SARS-CoV-2 and Herpes Simplex Virus: Insights from Three Case Reports - Bakti FU; Sufiawati I (International Medical Case Reports Journal)
Fitrah Utari Bakti,1,* Irna Sufiawati2,* 1Oral Medicine Residency, Faculty of Dentistry, Universitas Padjadjaran, Bandung, Indonesia; 2Department of Oral Medicine, Faculty of Dentistry, Universitas Padjadjaran, Bandung, Indonesia*These authors contributed equally to this workCorrespondence: Irna Sufiawati, Department of Oral Medicine, Faculty of Dentistry, Universitas Padjadjaran, Jl. Sekeloa Selatan No. 1, Bandung, West Java, 40132, Indonesia, Email irna.sufiawati@fkg.unpad.ac.idIntroduction: The Behçet’s Disease Current Activity Form (BDCAF) is crucial for monitoring the progression and treatment efficacy of Behçet’s Disease (BD), an autoimmune disorder that can be triggered or exacerbated by viral infections. Herpes simplex virus type 1 (HSV-1) has long been recognized as a potential trigger for BD, as it can induce systemic inflammation and exacerbate symptoms. In contrast, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has recently emerged and may also initiate or worsen BD symptoms. This report examines three BD cases with oral manifestations specifically triggered by HSV-1 and SARS-CoV-2, comparing their clinical activity and treatment responses.Case: Three female patients, aged 29, 24, and 41 years, presented to the Oral Medicine Department with complaints of canker sores, along with genital and skin lesions and red eyes. Intraoral examination showed ulcerative, erosive, and white plaque lesions throughout the oral mucosa. The first patient was confirmed to have COVID-19 by the SARS-CoV-2 RNA test. The second and third patients had a two-year history of recurrent oral ulcerations with reactive IgG anti-HSV-1 tests. All patients were diagnosed with BD according to the International Criteria for Behcet’s Disease. The BDCAF measurements were conducted, showing a BD activity index score of 4 for the COVID-19-positive patient, while scores of 6 and 7 were recorded for the other two patients with seropositive HSV-1.Case Management: Medications provided include corticosteroid, antimetabolite, analgesic, antiviral, antifungal, antiseptic mouthwash, and multivitamin. All patients showed good clinical improvement after treatment.Conclusion: The BD activity index scores of a BD patient with COVID-19 were lower than those with HSV-1 infection. This difference may be due to the recent SARS-CoV-2 infection in the patient, whereas reactivation of chronic latent HSV-1 in the other patients likely contributed to a longer history of clinical manifestations, resulting in increased disease activity.Keywords: autoimmune disease, Behcet’s disease, SARS-CoV-2, HSV-1